Potensi Tumbuhan dan Tanaman Herbal Indonesia Sebagai Anti SPF - Adam Permana; Tria Alfina Damayanti; Nia Yuniarsih (Jurnal Health Sains, 2022)
UV radiation can have an adverse effect on the skin. One of the ways to prevent these bad effects is to use sunscreen. The ethanol extract of jeruju leaves contains several secondary metabolites in the form of flavonoids and phenolics so that it has the potential as a sunscreen agent. This study aims to determine the potential of Indonesian herbs and plants as anti SPF. The method used in this article is a literature review. The results of phytochemical screening, temugiring ethanol extract contains flavonoid, phenolic (tannin) compounds, and curcumin, all of which have the potential as antioxidants and are useful as active ingredients that have the potential as sunscreens. From the results obtained, the methanol and n-hexane fractions of kebiul leaves can be used as sunscreen ingredients, at concentrations of 600 ppm, 800 ppm and 1000 ppm are included in the suntan category (moderate to extra protection), which will slightly absorb UV- A, but most can absorb UV-B rays. The suntan category can still cause the skin to turn brown, but only temporarily. The SPF value of the ethanol extract of jeruju leaves can be seen in the table. Based on the table, the average SPF value of the ethanol extract of jeruju leaves increased with each increase in the concentration of the extract. The SPF value ranges from 0 to 100, and the ability of a sunscreen that is considered good is above the SPF 15 value. Based on the literature, it is stated that flavonoids are one of the natural compounds that have the potential as photoprotective agents because they have the ability to absorb UV rays and can be antioxidant compounds.